Joint specific power production in cycling: the effect of cadence and athlete level - Aasvold, A. (Journal of Science and Cycling, 2017)
Introduction When increasing cadence, there is increasing knee joint contribution and decreasing hip contribution to external power [1, 2]. Increasing power output leads to a decrease in knee contribution and an increase in hip contribution [2, 3]. Low cadence (<60 rpm) interval training is a widely used training method, but previous studies have primarily focused on cadences ranging from 60 to 180 rpm, without examining the effect of low cadence on joint contribution. The present study investigates joint-specific power production in recreational and elite cyclists during cycling at a range of different cadences.